THE HISTORICAL DEVELOPMENT OF OS-TRACODES AND THE PALAEOGEOGRAPHY OF EUXINIAN BASIN IN MIDDLE MIOCENE – PLIOCENE - DYKAN, N. I. (Institute of Geological Sciences, NAS of Ukraine, 2012)
Some aspects of the historical development of ostracodes of Euxinian basin in Middle Miocene-Pliocene are specified. There are ostracodes migratory connections between Paratethys basins (Euxinian, Pannonian, Dacic) and Mediterranean basin; he recurrence time of Miocene ostracodes; the time of forming and square of the reconstructed ranges (autochthonous, endemic, disjunctive, mosaic) of Miocene ostracodes in Miocene-Pliocene. The trend of the salinity oscillation in the Indol-Cuban depression in Middle Sarmatian, Maeotian, Pontian, Early Cimmerian was reconstructed.